UMISM software ... - Fastook, James (Zenodo, 2023)
Source code for the University of Maine Ice Sheet Model (UMISM) adapted for Mars, as well as results for the Hellas project (archived elsewhere). All can be made for MacOS with makefile command, although you will also need the grstrt files available in grstrt.zip. The main program executable is map5.x, run with the script map5.e. All input.data files must be preprocessed with unpack.e, which runs the executable unpack.x. Results can be viewed with packz.e (runs executable packz.x) that spawns a generic gmt script to draw the appropriate figure desired. Those gmt scripts (in generic-gmts.zip) themselves will run gmtmake_new.e (runs execuatable gmtmake_new.x) to extract appropriate results. There are many unused programs for various special purposes that are not necessary to run UMISM but are provided anyway. Running UMISM with a data file inputWW.data provided unpack.e WW WW map5.e WW WW ... various interactive commands to control UMISM packz.e WW WW WW ... label numbers, output interval, start and end times ... : {"references": ["Scanlon, K. E. (2016), Ice sheet melting throughout mars climate history: Mechanisms, rates, and implications, Ph.D. thesis, Brown University, Providence, RI.", "Fastook, J. L., and M. Prentice (1994), A finite-element model of Antarctica: Sensitivity test for meteorological mass balance relationship, Journal of Glaciology, 40 (134), 167\u2013175."]} ...